Second language pronunciation - Kirkova-Naskova, Anastazija (Vestnik za tuje jezike, 2019)
The aim of thepaper is to give a critical summary of the traditional and more alternative techniques and activities for pronunciation practice recommended in the literature. In the past few decades the theoretical approaches to teaching pronunciation have changed considerably, from giving a strong focus on the accurate production of individual speech sounds to shifting the focus onto the greater communicative relevance of connected speech and intelligibility. Approaching L2 pronunciation teaching is not an easy task, and it needs to be systematically dealt with. The paper discusses several decisions teachers need to make when choosing activities for pronunciation practice: se-lecting the type of phonological structure to practice, deciding on the speech mode, determining the structural level of practice, focusing on a particular type of instruction, establishing the degree of control of the structure that is practiced, and choosing which cognitive skill to enhance while practicing. With regard to the various techniques for teaching pronunciation, the analysis shows they have adapted accordingly in line with the different trends. Hence, while traditional activities such as automatic repetition, ear-training and explicit phonetic instruction are still considered effective, additional priority is given to activities for raising phonological awareness, communicative activities and techniques that adopt an interdisciplinary approach.
Keywords: didaktika jezika; fonološka zavest; izgovorjava; ponavljanje glasov; pouk fonetike; sporazumevalne dejavnosti; tuji jeziki; zaznavni trening